Developing a corporate governance reporting score for the Malaysian banking sector / Siti Nurain Muhmad, Hafiza Aishah Hashim and Mohd Hassan Che Haat. - Muhmad, Siti Nurain; Hashim, Hafiza Aishah; Che Haat, Mohd Hassan (Universiti Teknologi MARA Cawangan Selangor, 2016)
There is a limited study on banking institution in Malaysia, especially the ones related to the corporate governance reporting of banks. The main objective of this study is to develop the Malaysian Bank Governance Reporting Score (MBGRS) for banking institutions in Malaysia. In these recent years, Bank Negara Malaysia has issued guidelines on corporate governance for banking institutions. Thus, it leads to the development of bank governance reporting score in order to measure the commitment of bank towards corporate governance. The overall finding of bank governance reporting score revealed that there is a lack of reporting in areas such as Board Structures, Duties and Effectiveness, Accountability and Audit, and Shareholder Rights. The findings provide a signal to identify the lack of area for the improvement in corporate governance of the banking sector in Malaysia.